'For friendship and conversation': Martial Scotland's Domestic Castles. Issue 1 (November 2015) - MacKechnie, Aonghus
Abstract : 'You and I have a fundamental disagreement, ' Charles told me, when I last saw him. This was concerning the military potential of the buildings described in his book The Scottish Chateau . I have taken that 'fundamental disagreement' as my topic, and I present it as a tribute to Charles's always-challenging intellect. It is a privilege to write an article he would have delighted to cross-examine me on, and I'm sorry he's not here to do that. Disagree with him or not: his ideas continue to shape today's thinking.